2007
DOI: 10.1016/j.cell.2007.10.037
|View full text |Cite
|
Sign up to set email alerts
|

IAP Antagonists Target cIAP1 to Induce TNFα-Dependent Apoptosis

Abstract: XIAP prevents apoptosis by binding to and inhibiting caspases, and this inhibition can be relieved by IAP antagonists, such as Smac/DIABLO. IAP antagonist compounds (IACs) have therefore been designed to inhibit XIAP to kill tumor cells. Because XIAP inhibits postmitochondrial caspases, caspase 8 inhibitors should not block killing by IACs. Instead, we show that apoptosis caused by an IAC is blocked by the caspase 8 inhibitor crmA and that IAP antagonists activate NF-kappaB signaling via inhibtion of cIAP1. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

82
1,329
12
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,016 publications
(1,437 citation statements)
references
References 35 publications
82
1,329
12
3
Order By: Relevance
“…As previously reported, degradation of c-IAP-1/2 is critical for Tweak/TNFα-or SM/TNFα-induced cell death. 26,28,33 Yet, we observed that the level of Tweak-, agonist LTβR-or CmpAinduced c-IAP1/2 degradation was similar in NIK +/+ and NIK − / − MEFs, indicating that c-IAP1/2 depletion is not compromised in the absence of NIK (Figures 4f and g and Supplementary Figure S4c). Together, these results indicate that NIK acts downstream of complex I formation but upstream or at the level of RIP1/caspase-8 assembly.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…As previously reported, degradation of c-IAP-1/2 is critical for Tweak/TNFα-or SM/TNFα-induced cell death. 26,28,33 Yet, we observed that the level of Tweak-, agonist LTβR-or CmpAinduced c-IAP1/2 degradation was similar in NIK +/+ and NIK − / − MEFs, indicating that c-IAP1/2 depletion is not compromised in the absence of NIK (Figures 4f and g and Supplementary Figure S4c). Together, these results indicate that NIK acts downstream of complex I formation but upstream or at the level of RIP1/caspase-8 assembly.…”
Section: Resultsmentioning
confidence: 77%
“…Previous studies reported that, at least in certain cell types, Tweak-and SM-induced cell death relied on the NIK-dependent neosynthesis of endogenous TNFα via induction of the classical and/or the alternative NF-κB pathway. 11,26,27,33 We can rule out this possibility in our in vitro and in vivo genetic models. Indeed, we showed that Tweak-, LTβR agonist-or SM-induced NIK stabilization in MEFs is by itself not sufficient to induce cell death and that NIK deficiency protected the MEFs from TNFR1-mediated death induced by exogenous TNFα.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36,44 This conclusion is supported by the following lines of evidence: First, the TNFacatching antibody Enbrel fails to prevent BV6-induced cell death in primary CLL cells. Similarly, we recently described that BV6/Dexamethasone-induced cell death in childhood ALL occurs in a TNFa-independent manner.…”
Section: Discussionmentioning
confidence: 79%
“…1B and 2), in line with the reported function of Smac mimetic to trigger NF-jB activation upon depletion of cIAP proteins. 16,35 As Smac mimetics have been described to engage an NFjB-mediated, TNFa-driven autocrine/paracrine cell death loop, 9,16,35,36 we next investigated whether TNFa is required for BV6-induced cell death in primary CLL cells. However, addition of the TNFa-blocking antibody Enbrel failed to protect primary CLL cells against BV6-induced cell death (Fig.…”
Section: Bv6 Triggers Ciap Degradation Nf-jb Activation and Tnfaindementioning
confidence: 99%